O-C TOPOLOGY AND SIERPINSKI SPACE - Karim Lelo, Ali (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper we choose a different approach and propose a generalization of Sierpinski space by defining a topology analogous to Sierpinski topology with the general collection t which is form a topology on a non empty set C , and the definition of K. Khan [5] will be only special case , so the ( O-C topology) is introduced . We investigate some of the general topological characterization of it , and this has a very interesting applications especially the Sierpinski space which is result from the finite set C which containing only two points .